Physical Characteristics of Artificial Reef Post Deployed on 2017 in Trenggalek Damas Beach - Anda Putra R. Sirait; Oktiyas Muzaky Muzaky Luthfi; Andik Isdianto (Universitas Airlangga, 2021)
Damage to the coral reef ecosystem in the Damas Coast waters is caused by the behavior of using fishing gear that is not environmentally friendly. Based on the problem, there is a solution to lay 25 cube-shaped artificial reefs in 2017. The condition of artificial reefs that have been placed in the waters of Damas Beach within 2.5 years needs to be monitored to determine the physical characteristics of artificial reefs. Observation of physical characteristics is done visually by using the underwater photo transect method. The observation found 22 artificial reefs (AR) including physical characteristics; 15 AR is Buried by sediment; 1 AR covered by a net; 3 AR in a Tilted position and 4 AR in good condition. Three AR that was not found is considered to have disappeared or the entire structure has been buried by sediment.